(untitled) (The Pakistan Development Review, 2005)
Financial stability plays an important role in economic growth and leads to sustained development. As such, financial stability is gradually emerging as a distinct policy function. Safeguarding Financial Stability, by Garry Schinasi, explains why financial stability matters, what it means, and what challenges are involved in securing it. The book is divided into three parts and contains twelve chapters. Chapter 1 gives the outline of the book and provides answers to various related questions. It highlights the increasing importance of financial stability issues, pinpoints the need for an analytical framework, and describes the specific objectives and organisation of the book.